Why don't employers hire long-term unemployed entitled to a wage subsidy? The employer's perspective on subsidised employment. (February 2023) - Behrenz, Lars; Månsson, Jonas
Despite a generous system with high wage subsidies for the long-term unemployed and newly arrived immigrants, many Swedish employers do not make use of this opportunity. This study seeks to increase knowledge of why some employers use the opportunity and others do not. Both register and survey data and combined register and survey data are used. One finding is that employers lack information about the subsidy programmes, although employers that had previously employed subsidised workers were much more likely to employ them in the future. Thus, a key policy question is how to present these subsidies to employers to reduce this barrier. The study also found that some employers hired people from these groups from altruistic motives. However, some employers responded that they would not employ a person entitled to a subsidy, regardless of the content of the subsidy scheme.